2020
DOI: 10.1002/ptr.6984
|View full text |Cite
|
Sign up to set email alerts
|

A review on pain‐relieving activity of berberine

Abstract: As isoquinoline alkaloid naturally occurs in Coptis and Berberis species, berberine (BER) has shown anti‐oxidant, anti‐tumour, anti‐bacterial and hepatoprotective activities and beneficial effects against digestive, cardiovascular and neurological conditions. Also, BER antiinflammatory, pain‐relieving and anti‐cholinesterase activities were widely studied. The present overview discusses the analgesic effects of BER. Based on the literature, BER exerted pain‐relieving activity against diabetic and chemotherapy‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 58 publications
1
11
0
1
Order By: Relevance
“…Berberine ( 29 ) can also relieve pain in a variety of ways, such as downregulating TRPV1, suppression of NF‐κB pathway, regulating opioid receptors, anticholinesterase activity, etc. (Hashemzaei & Rezaee, 2021).…”
Section: Natural Alkaloids With the Activity Of Treating Cns Diseasesmentioning
confidence: 99%
“…Berberine ( 29 ) can also relieve pain in a variety of ways, such as downregulating TRPV1, suppression of NF‐κB pathway, regulating opioid receptors, anticholinesterase activity, etc. (Hashemzaei & Rezaee, 2021).…”
Section: Natural Alkaloids With the Activity Of Treating Cns Diseasesmentioning
confidence: 99%
“…Its chemical structure is represented in Figure 1 . In recent years, a large number of research confirmed that BBR has extensive pharmacological properties, such as anti-inflammatory ( Kuo et al., 2004 ), pain‐relieving ( Hashemzaei and Rezaee, 2021 ), anti-infective ( Aswathanarayan and Vittal, 2018 ), antitumor ( Liu et al., 2019 ),neuroprotective ( Luo et al., 2012 ) and modulate energy metabolism, which can be used to treat cancer ( Zhang et al., 2020 ), digestive ( Zou et al., 2017 ), metabolic ( Xu et al., 2021 ), cardiovascular ( Martini et al., 2020 ), and neurological diseases ( Kulkarni and Dhir, 2010 ). Formulas containing traditional herbal Coptis chinensis, has been used for thousands of years in traditional Chinese Medicine.…”
Section: Berberine For Metabolic Disordersmentioning
confidence: 99%
“…Berberine has been shown to display potent analgesic activity [32]. One study investigated berberine's role in visceral pain, observing that berberine antinociceptive activity was blocked by the administration of the opioid receptor antagonist naloxone or by selective mu and delta morphine receptor (MOR and DOR) antagonists [33], which suggests that berberine binding activities at MOR and DOR may be responsible for visceral pain analgesia [32]. Interestingly, berberine also has an effect on the endogenous opioid system due to its ability to easily cross the blood-brain barrier [34].…”
Section: Berberinementioning
confidence: 99%